Improving adhesion between Carbon Fibre Reinforcements and Alkali- Activated Cements. - de Muinck, Derk (My University, 2020)
Concrete is the most widely used material in the world and even though as a material it has a relatively low environmental impact the shear amount of it being used is cause for environmental concerns. Reducing the need for large quantities of concrete and nding alternatives materials are two ways to reduce its impact. This can be achieved by using carbon bre reinforcements instead of steel rebars as well as using slag cement instead of conventional Portland cement. This project seeks to improve the adhesion of carbon bre reinforcements to the slag cement by impregnating the bre bundles with a solgel. The bre bundles were individually impregnated in di erent solgel baths and embedded into slag cement pucks. The shear strength was subsequently measured through pullout testing and the degree of impregnation was examined under a microscope. A wide range of di erent solgels were tested and the purely inorganic solgels showed higher shear strengths than the textile reinforcements used in the industry today. The microscopy showed a thorough impregnation although it was di cult to quantify. While these results were promising there was a large amount of variance in the results due to the simplicity of the methods used. Future work should focus on re ning these methods and continue to expand upon the potential of the coatings studied in this project. i